Eksistensi Haki di Indonesia Pada Era Disrupsi - Putri Putri; Rahmi Zubaedah (Peneliti.net, 2023)
This study aims to identify and examine the problems of the existence of intellectual property rights or IPR in Indonesia in the era of disruption. The method used is descriptive qualitative with data collection techniques carried out by triangulation which combines interviews, observation and documentation studies, the data is then analyzed in three stages which include reduction, presentation and drawing conclusions. The results of the discussion show that IPR can be an asset not only for the individual creator, but also for the state. However, in Indonesia, Intellectual Property Rights cannot be applied properly due to various factors such as culture, economy and law